2022
DOI: 10.3390/ijms23084238
|View full text |Cite
|
Sign up to set email alerts
|

Are BPA Substitutes as Obesogenic as BPA?

Abstract: Metabolic diseases, such as obesity, Type II diabetes and hepatic steatosis, are a significant public health concern affecting more than half a billion people worldwide. The prevalence of these diseases is constantly increasing in developed countries, affecting all age groups. The pathogenesis of metabolic diseases is complex and multifactorial. Inducer factors can either be genetic or linked to a sedentary lifestyle and/or consumption of high-fat and sugar diets. In 2002, a new concept of “environmental obeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…BPA exhibits obesogenic properties that alter PPARγ mRNA expression in THLE-2 cells. The obesogenic properties include adipogenesis, stimulating lipid accumulation in adipose tissue and liver, and perturbs obesity-related cytokines levels (40,41). The expression of this adipogenesis gene or lipid sensor indicates an increase in lipid accumulation and adipogenesis in the liver in response to BPA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…BPA exhibits obesogenic properties that alter PPARγ mRNA expression in THLE-2 cells. The obesogenic properties include adipogenesis, stimulating lipid accumulation in adipose tissue and liver, and perturbs obesity-related cytokines levels (40,41). The expression of this adipogenesis gene or lipid sensor indicates an increase in lipid accumulation and adipogenesis in the liver in response to BPA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we focus on the effects of BPs on glucose homeostasis and pancreatic β-cell function and viability. Recent reviews have addressed diabetes, obesity, and nonalcoholic fatty liver disease ( 5 , 27 , 53 , 54 ).…”
Section: Bisphenolsmentioning
confidence: 99%
“…In several in vivo and in vitro studies, BPA exposure was shown to promote significant disturbances in glucose homeostasis and insulin sensitivity. Impairments in lipid metabolism and the promotion of fat accumulation were also observed [ 9 , 10 , 11 ]. In addition, epidemiological studies have reported that urinary and/or serum BPA concentrations are strongly associated with an increased incidence of obesity [ 12 , 13 , 14 ] and diabetes [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, BPS and BPF are structurally and chemically similar to BPA ( Figure 1 ); thus, they are expected to promote adverse effects by acting as endocrine disrupters [ 11 ]. Recently, BPS and BPF were reported to promote fat accumulation in adipocytes [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%